(4+u)(4u+3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

4+u=0

4u+3=0

Set the first factor equal to 0.

4+u=0

Subtract 4 from both sides of the equation.

u=-4

u=-4

Set the next factor equal to 0.

4u+3=0

Subtract 3 from both sides of the equation.

4u=-3

Divide each term by 4 and simplify.

Divide each term in 4u=-3 by 4.

4u4=-34

Cancel the common factor of 4.

Cancel the common factor.

4u4=-34

Divide u by 1.

u=-34

u=-34

Move the negative in front of the fraction.

u=-34

u=-34

u=-34

The final solution is all the values that make (4+u)(4u+3)=0 true.

u=-4,-34

Solve using the Square Root Property (4+u)(4u+3)=0